Assessment of Occupational Heat Stress in A Selected Indonesian Steel Mill - Fauzan Huwaidi Ridwan; Siti Marwanis Anua; Bayu Suryo Aji; Ris Nurdin; Muhammad Hidayat Rizky; Mila Tejamaya (Universitas Airlangga, 2023)
Introduction: Workers in the Indonesian steel manufacturing industry are subject to many heat stress risk factors, ranging from the equatorial climate to physically demanding work tasks which may result in heat- related illnesses and reduced worker productivity. Hence, a study was conducted at Steel Mill X to assess the level of heat stress among its workers, determine the association of related factors and to provide meaningful recommendations. Methods: This study uses a descriptive cross-sectional method to assess workers' heat risk level and its association with individual, occupational and heat stress symptoms. An online questionnaire was used to collect primary data yet WBGT monitoring data were provided by Steel Mill X as secondary data. Results: The heat stress risk level score ranged from 48 to 140 (M=89.8, SD=±31.0). 122 workers were in the very high-risk category (75.8%). Occupational factors which had a statistically significant association with heat stress risk category includes: work area, length of exposure, air movement, hot surfaces, confined space, clothing factors and WBGT; while heat stress-related symptoms which were associated include headache, fatigue, profuse sweating, extreme thirst and increased body temperature. The absence of significant association between individual factors and heat stress risk category eliminates it as a confounding factor, suggesting occupational factors was the main variable. Conclusion: Control measures such as improving the supply of drinking water and maintenance of cooling systems should be implemented as soon as possible to prevent heat stress among workers.